Factors related to food safety behavior in the safe food village program in Yogyakarta - Lestari, Puji; Padmawati , Retna Siwi; Lestari, Lily Arsanti (Universitas Gadjah Mada, 2024)
Purpose: Food safety is a prerequisite that must be met to prevent foodborne diseases. The Indonesian Food and Drug Authority has initiated the Safe Village Food Program in rural communities as one of the solutions to address food safety issues. The objective of this research is to investigate the relationship between knowledge, attitudes, community origin, and sociodemographic factors (age, marital status, gender, level of education) with food safety behaviors. Methods: This study uses secondary data with a cross-sectional design. The number of samples analyzed was 737 respondents. Results: The results show that the variables of community origin and attitude are associated with food safety behavior among the total respondents. Conclusion: The determining factors of behavior that need to be considered in the formulation of programs related to food safety are community characteristics and strengthening positive attitudes to encourage appropriate food safety behaviors.